The Impact of Including Immigrants without Permanent Residence Status in the Public Health Insurance System in the Czech Republic - Jana Tepperová; Hana Zídková (Review of Economic Perspectives, 2016)
Whether an individual can or cannot participate in the Czech public health insurance system depends on several characteristics, one of which is whether he/she has permanent residence status in the Czech Republic, and a second whether he/she is employed. This means that those without permanent residence status, including self-employed migrants from third countries, their dependent relatives, and the dependent relatives of third country employees in the Czech Republic, cannot participate in the public health insurance system. Some argue that such migrants should be included in the system, since commercial health insurance is disadvantageous and the contributions they would pay into the public health insurance system would increase the public health insurance agencies' income. We estimate the value of the contributions to public health insurance that would be paid by third country self-employed and non-working immigrants, if they were insured based on data from 2011 to 2013, and compare this to the assumed costs of their medical care. To calculate the contributions for self-employed migrants we use data on the distribution of the tax base for self-employed persons from personal income tax returns. Our estimation results in an overall negative balance of 22 million CZK on the data for 2012 and 2013. In the current system this deficit would be covered by the state, which would pay contributions to the system for certain (state insured) persons amounting to 97 million CZK; overall therefore the inclusion of these immigrants would result in a positive balance of 75 million CZK.
Keywords: 330